ARTIFICIAL INTELLIGENCE TECHNOLOGY AS A DRIVER OF INVESTMENT AND ECONOMIC INNOVATION - St. Hatidja; Jamaluddin Jamaluddin; Ida Ilmiah Mursidin (Adisam Publisher, 2025)
This research examines the impact of artificial intelligence (AI) technology on investment promotion and encouragement of economic innovation. The purpose of this study is to understand the dynamics in which AI serves as a catalyst for economic growth and modern industrial transformation. The research method used in this study is literature review. The results show that a coordinated approach between these stakeholders is important to maximize the economic potential of AI technologies, while also taking into account the ethical, privacy, and security challenges that arise. This research contributes to a broader understanding of the transformative impact of AI on the global economy and offers strategic guidance for the integration of this innovative technology into the economy of the future.